ADVANCEMENT OF THE ECC ALGORITHM TO PREVENT MAN-IN-THE-MIDDLE AND REPLAY ATTACKS - Ahamed, Bazeer; Kareem, Fajlul; Noor Mohamed, Mohamed Yasin (Procedia computer science, 2025)
It is evident from recent studies that a variety of security-related approaches and their applications have been used. There are numerous cryptographic algorithms that are applied successfully and efficiently in a variety of security-related applications. Notably, the attacks can be divided into two categories. There are two types of attacks: active and passive. The passive assault is used in an experiment to obtain information without authorization. Passive attacks, for instance, include actions like listening and intercepting on a communication channel. The attacker then attempts to access the data and alter it in an unauthorized way in this active attack. A man-in-the-middle attack is the best illustration of an active attack. In this case, the attacker sends the message’s public key as the host’s public in an attempt to hack it. In order to overcome this issue, cipher text must be obtained by both the sender and the recipient encoding a code bit. This bit is used to identify who owns the public key—the attacker or the sender. The recipient is free to communicate when the sender has been identified. This information is used to identify who owns the public key—the attacker or the sender. The addressee can speak freely when the sender has been identified.